Pengaruh Kesadaran Wajib Pajak, Pengetahuan Wajib Pajak, Kualitas Pelayanan, Sanksi Perpajakan, dan Motivasi Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Safitri, Nadila; Nugroho, Arief Himmawan Dwi (Universitas Islam Negeri Alauddin Makassar, 2024)
The study is intended at exploring and identifying in depth how different factors influence the level of compliance with tax obligations. To obtain representative data, a random sampling method was applied, and 100 respondents were selected to participate. Data collected from respondents was then analyzed using double linear regression techniques, which allowed researchers to measure and assess the relationship between each factor studied and compliance with tax obligations in a comprehensive manner. Specifically, high awareness of tax liability contributes greatly to increased tax compliance. In addition, in-depth knowledge of tax regulations also plays an important role in determining how obedient a person is in fulfilling his or her tax obligations. The quality of tax authorities also plays a role in improving compliance, with good service inclining to inspire taxpayers to comply more. Moreover, implementation of rigorous and consistent tax sanctions has also been shown to improve compliance with tax obligations. In other words, this study provides evidence that awareness of tax obligations, a good understanding of tax regulations, adequate quality of service from tax authorities, effective enforcement of sanctions, and individual motivation play an important role in improving tax compliance. These findings confirm the importance of focusing on these and provide valuable insights for future tax policies. Keywords: Taxpayer Awareness, Tax Knowledge, Service Quality, Tax Sanctions, Taxpayer Motivation, Taxpayer Compliance